Клинический пример исправления сочетанных ошибок ранее проведенного неудачного эндодонтического вмешательства с использованием дентального операционного микроскопа и ультразвуковых модифицированных насадок из стали и титан-ниобиума (Эндодонтия Today)
This paper presents a complex clinical case of endodontic retreatment of molar with associated defects - metal instrument fracture and two perforations of the canal walls of different localization - in two visits. The process of endodontic treatment is made possible through the use of an operating microscope in dental clinic, which allowed to specify the anatomical structure of root canal, with the help of magnification and increased illumination in order to facilitate the implementation of the basic stages of preparation, sealing, ultrasonic cleaning, extraction of fragmented tools, and finally, a tight sealing the perforations.